Cross-Dysregulation of O-GlcNAcylation and PI3K/AKT/mTOR Axis in Human Chronic Diseases - Very, Ninon; Vercoutter-Edouart, Anne-Sophie; Lefebvre, Tony; Hardivillé, Stéphan; El Yazidi-Belkoura, Ikram (Frontiers in Endocrinology, 2018)
The hexosamine biosynthetic pathway (HBP) and the phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) kinase signaling pathway are considered as nutrient and metabolic cellular sensors that regulate a wide panel of essential biological processes. HBP generates uridine diphosphate N-acetylglucosamine (UDP-GlcNAc), the substrate for O-GlcNAc transferase (OGT), the enzyme that O-GlcNAcylates proteins on serine (Ser) and threonine (Thr) residues. O-linked β-N-acetylglucosaminylation (O-GlcNAcylation) and phosphorylation are highly dynamic post-translational modifications occurring at the same or adjacent sites and that regulate folding, stability, subcellular localization, partner interaction or activity of protein targets. In this review, we summarize recent evidences of a connection between O-GlcNAcylation and PI3K/Akt/mTOR pathways in both physiological and pathological contexts. We also emphasize the cross-dysregulation of these pathways that influences development of chronic human diseases such as cancer, type-2 diabetes mellitus (T2DM), cardiovascular and neurodegenerative diseases.